The Invisible Plagues: A Conceptual Model of the Neglect of Neglected Tropical Diseases - Bryanna Mantilla (Social Medicine Publication Group, 2011)
Neglected tropical diseases (NTDs) affect at least 1 billion people worldwide and are estimated to threaten millions more. NTDs are widespread, primarily affect socially marginalized and vulnerable populations, and contribute to and reinforce global poverty. Although NTDs have significant medical, social, economic and political implications, they receive low priority in global health policies. Moreover, the existing literature has not yet examined the inherently social linkages of NTDs to global inequality, power and "development." This article takes a critical sociological approach in order to construct a conceptual model to explain NTDs' "neglect." Distal level factors in the model include: global inequality and non-modifiable biological aspects (geographic isolation, chronic and disfiguring disease outcomes and concurrent infections). Intermediate level factors include: poverty and neoliberal health policy. Proximal level factors include: lack of research and development; lack of funding for interventions; the dominance of disease-specific interventions; lack of infrastructure and medical services; social isolation; epidemiological methods that underestimate NTDs' disease burden; and social stigma. Further refinement of such a model may enable global health advocates to create more effective and comprehensive strategies to end not only the "neglect" of NTDs but the social contexts that have created this "neglect."